The effect of reputation and electronic word of mouth on customer trust - Henri Mailudin; Gugyh Susandi (Marketing Management Studies, 2021)
The purpose of the study was to determine the effect of reputation and electronic word of mouth on customer trust in the Lazada marketplace. The method used in this research is a quantitative method with survey research. The sample selection was done by using purposive sampling technique with a total sample of 100 respondents. The data used is interval data. The statistical method for testing the data is using the SPSS 22 program. By using multiple linear regression analysis, the results of the equation Y= 1.874 + 0.310X1 + 0.210 X2 + e. From the research results, it is known that reputation and electronic word of mouth influence partially or simultaneously on customer trust. From the results of this study, it is known that reputation and electronic word of mouth on customer trust only have an effect of 0.81 or 86.1%, meaning that there are other factors in increasing customer trust that require further research.